A facile method for anti-cancer drug encapsulation into polymersomes with a core-satellite structure - Hongchao Xu; Weiwei Cui; Zhitao Zong; Yinqiu Tan; Congjun Xu; Jiahui Cao; Ting Lai; Qi Tang; Zhongjuan Wang; Xiaofeng Sui; Cuifeng Wang (Taylor & Francis Group, 2022)
Polymersomes possess the self-assembly vesicular structure similar to liposomes. Although a variety of comparisons between polymersomes and liposomes in the aspects of physical properties, preparation and applications have been elaborated in many studies, few focus on their differences in drug encapsulation, delivery and release in vitro and in vivo. In the present work, we have provided a modified direct hydration method to encapsulate anti-cancer drug paclitaxel (PTX) into PEG-b-PCL constituted polymersomes (PTX@PS). In addition to advantages including narrow particle size distribution, high colloid stability and moderate drug-loading efficiency, we find that the loaded drug aggregate in small clusters and reside through the polymersome membrane, representing a unique core-satellite structure which might facilitate the sustained drug release. Compared with commercial liposomal PTX formulation (Lipusu®), PTX@PS exhibited superb tumor cell killing ability underlain by multiple pro-apoptotic mechanisms. Moreover, endocytic process of PTX@PS significantly inhibits drug transporter P-gp expression which could be largely activated by free drug diffusion. In glioma mice models, it has also confirmed that PTX@PS remarkably eradicate tumors, which renders polymersomes as a promising alternative to liposomes as drug carriers in clinic.